Standar Isi Pada Manajemen Kurikulum Lembaga Pendidikan Buddha (Tinnjauan Kesiapan Keberadaan Sekolah Minggu Buddha Di Indonesia) - Suherman Suherman; Hadion Wijoyo; Kresno Budoyo; Nur Amim; Suryani Suryani (Universitas Persada Indonesia YAI, 2022)
In practice, article 12 paragraph (1) of Law no. 20 of 2003 concerning the National EducationSystem has not been implemented effectively with the existence of schools that do not provideservices for Buddhist subjects so that the function of Buddhist religious education carried out nonformallyby Buddhist educational institutions is very important to complete the formal education.This paper aims to provide an overview of content standards in curriculum management inBuddhist educational institutions on the readiness of the existence of Buddhist schools inIndonesia in the future. The research method used is qualitative by means of a literature study;collected several articles, books, journals, regulations and Buddhist Laws and Suttas as well asseveral reference sources related to Curriculum Management in Buddhist Educational institutions.The results of this study found that the Buddhist Sunday School Curriculum as stipulated in theDecree of the Director General No. 63 of 2017 has referred to the National Education contentstandards, as well as the Nawa Dhammasekha curriculum. This curriculum is in accordance withthe core competencies and competencies of graduates, so it can also be used as a reference forcurriculum preparation for Buddhist schools in the future. In addition, Buddhist educationalinstitutions must really be able to implement curriculum management in a professional manner sothat the quality of Buddhist and Buddhist education can increase and meet the goals of nationaleducation and Buddhist education itself, and if the opportunity to establish a Buddhist school isopen, Buddhist Educational institutions already prepared with an appropriate curriculum and witha professional curriculum management, this will be a contribution as well as a solution to the gapsthat arise from the ineffective implementation of article 12 paragraph (1) of Law no. 20 of 2003.